The Role of HSP70 in Sperm Quality - Payan-Carreira, Rita (2020)
Heat shock proteins (HSP) constitute a large family of proteins that are most conserved in living organisms. The 70 kDa HSP (HSP70) is one of its most abundant members. Under normal conditions, they are constitutively expressed in cells, playing several physiological functions as molecular chaperones. HSP are generally associated with cellular response to an eclectic variety of stimuli, such as oxidative stress, hypoxia-ischemia, nutrient deprivation, and apoptosis signalling. HSP are widely distributed in mammal tissues and particularly in those associated with reproduction, such as the endometrium, trophoblast, placenta, or testicles. Two forms of testis-specific HSP70 have been localized in spermatogenic cells. They are thought crucial to germ cell differentiation and sperm production. These chaperone molecules have also been found in the sperm surface in different species. Situations of male infertility associated with heat or osmotic stress have been implicated in altered expression of HSP. Besides, it was demonstrated HSP70 molecules to suffer a dynamic redistribution at the sperm surface during capacitation and acrosome reaction. It has been proposed HSP70 molecules present in semen to modulate the immune system of the female reproductive tract after ejaculation, protecting the spermatozoa against disruptive stressors. During the preparation of seminal doses, when sperm is separated from the seminal fluid, this protective effect is withdrawn, and the sperm cells became more susceptible to the effects of environmental changes. Different studies showed a decrease in the HSP70 content of sperm submitted to freezing/thawing or sperm sorting processes, in association with its redistribution at the sperm surface. These features have been associated with loss of sperm function after manipulation that mimics that of capacitation. HSP70 was also found to be disturbed in male infertility. It is running with poor semen quality, which might explain some cases of idiopathic conditions in the absence of dysfunctional sperm. This review intends to discuss the roles of the HSP70 family in spermatogenesis and sperm function, detailing the mechanisms that may foster sperm quality and the use of HSP as markers of fertility.